MULTIKULTURALISME KEBUDAYAAN DAERAH CIREBON - Reiza D. Dienaputra; Agusmanon Yunaidi; Susi Yuliawati (PANGGUNG, 2021)
Cirebon has a very heterogeneous population. The heterogeneity of the Cirebon Population goes through a very long process, going on since the early days of the Cirebon Sultanate in the XV century. Along with the heterogeneity of its population, Cirebon culture has developed into a culture that is full of diversity, as well as representing cultural diversity in equality. This reality is interesting to observe, especially to find out about how multiculturalism is in Cirebon culture and how the elements of multiculturalism are represented in Cirebon culture. To reveal all this, the historical method is used, which consists of four stages of work, namely, heuristics, criticism, interpretation, and historiography. The results of research on several objects of the advancement of Cirebon culture has a correlation with the heterogeneous population of Cirebon. The cultures that contributed to the birth of a multicultural Cirebon culture were Indian, Arabic, Chinese, Western, Sundanese and Javanese culture. The cultural reality of Cirebon, which is full of cultural diversity, certainly needs to be maintained and preserved as well as being a model for strengthening national integration.